2005
DOI: 10.1097/00003446-200508000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Development of Visual Attention Skills in Prelingually Deaf Children Who Use Cochlear Implants

Abstract: Objective-To determine the effects of length of cochlear implant use and other demographic factors on the development of sustained visual attention in prelingually deaf children and to examine the relations between performance on a test of sustained visual attention and audiological outcome measures in this population.Design-A retrospective analysis of data collected before cochlear implantation and over several years after implantation. Two groups of prelingually deaf children, one >6 years old (N = 41) and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
73
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 43 publications
(138 reference statements)
13
73
1
2
Order By: Relevance
“…These results are similar to those gathered by Horn, Davis, Pisoni and Miyamoto (2005) who carried out a study that aimed to analyze the development of attention skills in children with cochlear implants. They demonstrated that even though after the implantation process the children continued to present very poor results in the tasks aimed at evaluating their ability to sustain their attention, these results improved slightly after several years using the cochlear implant.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are similar to those gathered by Horn, Davis, Pisoni and Miyamoto (2005) who carried out a study that aimed to analyze the development of attention skills in children with cochlear implants. They demonstrated that even though after the implantation process the children continued to present very poor results in the tasks aimed at evaluating their ability to sustain their attention, these results improved slightly after several years using the cochlear implant.…”
Section: Introductionsupporting
confidence: 87%
“…Furthermore, along the lines of Dye and Hauser (2014), Horn, Davis et al (2005) and Yucel and Derim (2008) it is important to note the high percentage of classroom teachers and speech, language and hearing specialist teachers who expressed that the implanted students displayed difficulties to stay attentive throughout the completion of tasks. Some studies (Quittner et al, 2007, Quittner et al 1994Smith, Quittner et al1998) suggest that even though in the months following implantation there are substantial improvements in the tasks that require greater and sustained visual attention, it is not until the children have reached 8 or 9 years of age that they are able to make better use of the cochlear implant due to the strong relationship that exists between the level of performance required in each task and the age of the children.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, auditory deprivation has been implicated in reorganization of visual attention processes to favor a wider spatial distribution of selective attention (Bavelier et al 2000(Bavelier et al , 2001Proksch and Bavelier 2002;Rothpletz et al 2003). Furthermore, the development of sustained attention in children with PLD may be positively influenced by the degree of early auditory access (Quittner et al 1994;Smith et al 1998;Horn et al 2005). Obviously, children with better behavioral control, selective and sustained attention could be expected to be better at any psychoacoustic task including amplitude modulation detection.…”
Section: Tablementioning
confidence: 99%
“…Only one survey focused on the visual skills 32 . When comparing groups of children with normalhearing and cochlear implant users in visual attention tasks, the study found that cochlear implant users showed improved visual attention after two years of using the device, with gains in reading and writing processes.…”
Section: Analysis By Approached Skillmentioning
confidence: 99%